Commodity Prices and Inflation Expectations in the United States - Celasun, Oya (IMF Working Papers; Working Paper, 2012)
U.S. monetary policy can remain extraordinarily accommodative only if longer-term inflation expectations stay well-anchored, including in response to commodity price shocks. We find that oil price shocks have a statistically significant, but economically small impact on longer-term inflation compensation embedded in U.S. Treasury bonds. The estimated effect is larger for the post-crisis period, and robust to controlling for measures of liquidity risk premia. Oil price shocks are also correlated with the variance of longer-term inflation expectations in the University of Michigan Survey of Consumers in the post-crisis period. These results are not attributable to looser monetary policy - oil price increases were associated with expectations of a faster monetary tightening after the crisis. Overall, the findings are consistent with some impact of commodity prices on long-term inflation expectations and/or on inflation rate risk.